Incompetent cervix: state-of-the-art - Kuznetsova O.V; E.V. Zarubeeva (LCC «Medicine-Inform», 2019)
O.V. Kuznetsova1, E.V. Zarubeeva2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2N.V. Sklifosovsky Research Institute of First Aid, Moscow, Russian Federation This article provides a systematic analysis of published data on incompetent cervix and its role in miscarriage and premature birth and addresses novel pathogenetically oriented management algorithms for this condition. The paper discusses foreign and domestic articles published over the previous two decades. Potential risk factors for incompetent cervix and its role in miscarriage and premature birth are described. Considering that incompetent cervix should be addressed immediately to prevent premature birth being required to select management strategy (surgery or conservative approach), current modalities for early diagnosis and treatment depending on incompetent cervix pathogenesis and obstetrical scenario are compared. Every study in this branch of obstetrics should be considered as a step to overcome this complication of pregnancy as well as to reduce the rate of miscarriage and premature birth. Keywords: incompetent cervix, cervical cerclage, obstetrical pes sary, micronized progesterone, miscarriage, premature birth. For citation: Kuznetsova O.V., Zarubeeva E.V. Incompetent cervix: state-of-the-art. Russian Journal of Woman and Child Health. 2019;2(4):286-291.